2013
DOI: 10.1016/j.clinph.2012.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal oscillations in the EEG under varying cognitive load: A comparative study between slow waves and faster oscillations

Abstract: the support of our participants, Suzannah Helps (Developmental Brain-Behaviour Laboratory, School of Psychology, University of Southampton, UK) for her contributions to the task design, and Daniel Durstewitz (Central Institute of Mental Health, Mannheim, Germany) for useful comments on the manuscript. We also thank all three anonymous reviewers for their constructive comments. AbstractObjective: This study has been specifically designed to investigate very low frequency neuronal oscillations (VLFO, <0.5 Hz) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
(119 reference statements)
0
15
0
Order By: Relevance
“…The key aim of the present study is to address this issue by comparing the level of VLF oscillation attenuation occurring in the transition from rest to two types of waiting task to that seen in the transition from rest to a simple cognitive reaction time task. Direct current EEG (DC-EEG) was used to measure VLF oscillations as it has excellent temporal resolution and offers a more direct measure of neural activity than BOLD signals (Demanuele et al, 2013). The current study builds on previous research which has identified a robust resting state VLF EEG network with high spatial stabilitiy and temporal reliability (Helps et al, 2008).…”
Section: Introductionmentioning
confidence: 91%
“…The key aim of the present study is to address this issue by comparing the level of VLF oscillation attenuation occurring in the transition from rest to two types of waiting task to that seen in the transition from rest to a simple cognitive reaction time task. Direct current EEG (DC-EEG) was used to measure VLF oscillations as it has excellent temporal resolution and offers a more direct measure of neural activity than BOLD signals (Demanuele et al, 2013). The current study builds on previous research which has identified a robust resting state VLF EEG network with high spatial stabilitiy and temporal reliability (Helps et al, 2008).…”
Section: Introductionmentioning
confidence: 91%
“…Our study supports the view that in terms of spontaneous brain activity, waiting, despite some characteristics in common with resting, is similar to other goal-directed activities such as performing information processing tasks. Prior debates about the functional status of EEG-VLFO as a measure of real neuronal activity, and the extent to which it is functionally similar to BOLD oscillations (Demanuele et al, 2013;Vanhatalo et al, 2005), notwithstanding, the localization of sources to midline structures in the current study raises new questions about the relationship between the EEG-VLFO network and the DMN. Indeed recent studies using simultaneous EEG-fMRI recordings have identified a direct association between spontaneous BOLD signals and EEG in both infra-slow (Hiltunen et al, 2014) and higher frequency domains (Laufs et al, 2003;Mantini et al, 2007).…”
Section: Discussionmentioning
confidence: 85%
“…Adding rate adaptation to this model is motivated by the physiological importance of slow oscillations of LFPs (Steriade et al 1993, Demanuele et al 2013) and data implicating a related role for rate adaptation. Slow oscillations (~0.1-1 Hz) are sometimes parsed into Up and Down states (Steriade 2006), where rate adaptation is thought to play a role in the transitions (Destexhe et al 2007).…”
Section: Introductionmentioning
confidence: 99%